In-situ measuring and predicting dynamics of soil bulk density in a non-rigid soil as affected by tillage practices: Effects of soil subsidence and shrinkage - Wang, Yuekai; Zhang, Zhongbin; Guo, Zichun; Chen, Yueming; Yang, Junsheng; Peng, Xinhua (Soil & tillage research, 2023)
Non-rigid soils (e.g., Vertisols) present dynamics of bulk density (ρb) due to high shrinkage and swelling. However, the in-situ measurement and prediction of the dynamic of ρb in non-rigid soils are still great challenges. The objectives were to (1) evaluate the performance of the combined soil moisture and thermal property sensors in estimating in-situ ρb dynamics under different tillage practices, (2) and establish mathematic equations to predict the ρb dynamics associated with soil subsidence and shrink-swelling processes during wetting and drying cycles. The in-situ ρb monitoring and periodical intact soil core sampling were conducted in the 0–10 cm and 10–20 cm layers in a Vertisol under three tillage treatments, containing no-tillage (NT), rotary tillage (RT) and deep ploughing (DP). Our results showed that the dual-sensor combination provided accurate ρb estimates in the field over 2021–2022 year (R2 > 0.487, RMSE < 0.177 g cm−3), except for the early stage after deep tillage. The ρb dynamics in the 0–20 cm in the NT and the 10–20 cm layer in RT treatment were mainly caused by shrink-swelling. Whereas the ρb dynamics in the 0–10 cm and 10–20 cm in the DP and the 0–10 cm layer in RT treatment were predominantly determined by soil subsidence first and then shrink-swelling when the accumulative rainfall (Pt) reached 131.8 mm, 186.1 mm, and 79.3 mm, respectively. The ρb dynamics during soil subsidence were well-fitted by an exponential equation related to accumulative rainfall (R2 > 699, P < 0.01), while the ρb dynamics during shrink-swelling were well-fitted by a newly proposed SSCρb equation derived from the Peng and Horn soil shrinkage model (R2 > 589, P < 0.05). Combined with the long-term monitored rainfall and soil moisture, The SSCρb equation and the two-stage equation involving subsidence and SSCρb exhibited good prediction of ρb dynamic from 2017 to 2022 (R2 > 0.453, RMSE < 0.070 g cm−3). The soil subsidence and shrink-swelling process accounted for 3.32%− 12.5% and 2.84%− 14.8% of the ρb variation in tilled non-rigid soils, respectively. Our results demonstrated that the dual-sensor combination can be applied for field ρb monitoring in non-rigid soil. The proposed two-stage equation has great potential for predicting the field dynamics of ρb. •The dual-sensor combination showed good estimation of in-situ ρb dynamic in a Vertisol.•The dynamic of ρb was predominantly driven by shrink-swelling in the no-tillage treatment.•A two-stage equation involving both soil subsidence and shrink-swelling was established.•The ρb dynamic was well predicted by the two-stage equation in the deep tillage treatment.